Lycopersicon esculentum 'Indigo Rose': A new horizon in tomato farming - Gomes , Elienae da Silva; Schipfer, Caroline Wolf Trentini; de Freitas, Marina Melliny Guimarães; Friedrichsen, Jéssica de Souza Alves; de Oliveira, Veridiana de Almeida Flores; da Silva, Isabela Carolina Ferreira; de Castro, Fernanda Francielle; de Resende, Francine Rubim; Madalena, Tais Cristina Coelho Alves; Júnior, Oscar de Oliveira Santos (Seven Editora, 2024)
The tomato variety Lycopersicon esculentum 'Indigo Rose', recognized for its distinctive purple coloration and high anthocyanin content. Developed to improve disease resistance and increase nutritional benefits, this tomato variety stands out for both its aesthetics and its health benefits.In this context, the present study aimed to address the botanical and genetic characteristics of 'Indigo Rose', which led to its creation. Agronomic aspects are presented, including recommendations on cultivation practices, from soil preparation to harvesting. Resistance to pests and diseases, along with adaptability to different climatic conditions, is highlighted as a key factor for success in growing this variety.The nutritional benefits of 'Indigo Rose' are widely discussed, with an emphasis on anthocyanins and their antioxidant effects, furthermore, it presents the economic and market impact of this variety, underscoring the growing demand for functional and visually appealing foods among health-conscious consumers. DOI:https://doi.org/10.56238/sevened2024.023-009